The Effect Of Consuming Pineapple Juice (Ananas Comusus [L] Mer) Towards The Duration Of The Stage I Latent Phase - Susi Irianti; Siti Sugih Hartiningsih; Achmad Suwardi (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2019)
In Indonesia, prolonged delivery is one of the cause of Maternal Mortality. The prolonged delivery which occurs in the latent phase is also called prolonged latent phase, a labor which lasts over eight hours of labor in primigravida. This research was started by the society’s custom of consuming fruits that are beneficial to smooth a labor process, consuming pineapples. Pineapples contain high amounts of vitamin C, sugar, vitamin A, a number of minerals, and an enzyme called bromelain. Bromelain is an enzyme that stimulates the production of prostaglandin. The increased prostaglandin causes contractions in the uterine muscle so that labor occurs. This study aims to determine the effect of pineapple juice towards the duration of the first stage of the latent phase. The method of this research was quasi experimental. The study was conducted in July to September 2018 at Ciruas Public Health Center, Serang, Banten. The sample in this study was 80 mothers in latent phase. Sampling was taken by using consecutive sampling technique. The analysis of timing differences in umbilical cord detachment was tested by using the Mann Whitney statistical test. The result shows that the average length of time in the first stage of the latent phase in the intervention group was 91,53 minutes, which was 57,75 minutes faster compared to the control group’s length of time, 149,28 minutes. There was a significant difference in the group given pineapple juice with those who were not given pineapple juice with p value 0,002 (α <0,05). Giving pineapple juice can accelerate the duration of the stage I latent phase in primigravida because pineapples contain an enzyme called bromelain and serotonin. The consumption of pineapple can be a solution for nutrients consumed when labor started at the first stage of latent phase and make the time period of the latent phase shorter and reduce the risk of intervention during labor.